Microdiscectomy for Lumbar Intervertebral Disc Prolapse: Is Fixation Required? - Patankar, Amey P.; Chaudhary, Shivani; Patel, Kashyap (Indian Journal of Neurosurgery, 2023)
Introduction Microdiscectomy, as of now, is considered the gold standard for the treatment of herniated lumbar disc. It preserves motion at the spinal segment and does not alter the local spinal anatomy significantly, resulting in a “functional and mobile” spine. Development of increasingly better-quality implants has seen their indiscriminate use in cases without any demonstrable instability. We see an increasing number of patients of lumbar disc prolapse being treated by fixation and fusion procedures, without any clear indication or evidence supporting such practice. This adds to the operating time, blood loss, cost of surgery and leads to loss of motion at the spinal segment resulting in a “stiff and immobile spine.” Our 10-year experience of treating lumbar disc herniation by micro-discectomy makes a strong case for preserving the spinal motion segment wherever possible and to use fixation very judiciously only in cases of proven instability.Materials and Methods A total of 295 cases of lumbar disc prolapse operated by the first author from January 2013 to April 2022 were analyzed. All the patients had unilateral or bilateral radicular pain. Preoperatively instability was ruled out by dynamic X-rays. All the patients were operated in prone position on Wilson's frame. Microdiscectomy was done through the inter-laminar space. Patient outcomes and complications were analyzed.Results There was no mortality in our series. All the patients had significant relief of lower limb pain with improved visual analog scale scores postoperatively. The patients were followed up for 6 months. There were complications in 17 patients, all of which were treated successfully with a good outcome. None of the complications were attributable to failure of doing fixation.Conclusion Lumbar disc prolapse can be treated effectively by microdiscectomy. Fixation should be reserved for only those cases with demonstrable preoperative instability.
Keywords: microlumbar discectomy; lumbar disc prolapse; fusion